DETAMAL (ANTI-THEFT DETECTOR) : THEFT CASE PREVENTION DETECTOR APPLICATION OF MICROCONTROLLER ARDUINO UNO BASED AS HOME SECURITY SYSTEM - Ardian, Zalfie; Dewi, Sarini Vita (Ubudiyah Indonesia University, 2016)
ABSTRACTThe increasing criminal case nowadays makes people worried aboutlosing their properties. In addition, they do not hesitate to act anarchist andoften hurt the victim. These criminals frequently come to the victim's houseto perform the act of theft. However, theft is often successfully thwartedonly by a shout or alarm sound that makes the thief to be panic and afraidthen run while cancelling his intention to proceed with his action.Therefore the authors wanted to create an automatic detection system byrelying on Arduino UNO, PIR sensor as motion detector and equipped witha camera that will capture images right after the sensor sounds and thesound is expected to thwart the robbery action. The advantages of thisapplication is the camera will rotate automatically where the sensors thatdetect the presence of the thief detected. And the resulting sound is alsoderived from the micro SD memory card with MP3 format so that the userscan use the sound of shouting, guard dog, or siren that will make the thiefpanic and run.Keywords : Arduino Uno, Detector, PIR sensor, Theft